UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK KELAS XI MIA 6 SMAN 9 PEKANBARU PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS - Mullia Wahyuni; Rasmiwetti Rasmiwetti; Asmadi M. Noer (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The classroom action research is consisting two cycles. The research purpose is to know activities and learning outcomes of students SMAN 9 Pekanbaru, especially on chemistry subject, solubility equilibrium by used talking chips cooperative model. Subjects research are 39 students, class XI MIA 6 which consisted 17 boys and 22 girls students. Techniques used to collect data include observation and tests. Data analysis using descriptive analysis. The results showed that the percentage of learning activities of students I cycle of 64.58% increased in cycle II to 81.25%. The percentage of students' learning outcomes also increased in cycle I by 64.10% to 89.74% in cycle II. Based on the research results, it can be concluded that the application of cooperative learning model type of talking chips can improve the activity and learning outcomes of students Class XI MIA 6 SMAN 9 Pekanbaru On the subject of Solubility Equilibrium.Key words: Activity, Learning outcomes, Talking Chips, Solubility Equilibrium